Genotypic characterization of amoeba isolated from Acanthamoeba keratitis in Poland - Derda, Monika (Parasitol Res, 2015)
Free-living amoebae belonging to the genus Acanthamoeba are the causative factor of many diseases. Among others, they cause Acanthamoeba keratitis (AK), a condition that usually occurs in contact lens wearers, though it is also observed in non-wearers. The number of diagnosed cases of AK increased more than eightfold during 8 years in the USA, and a proportional increase in frequency also occurred in Poland and Europe. Cases of AK are usually diagnosed late, and their therapy is difficult and rarely successful. AK is an uncommon diagnosis in Poland. The increased number of positive cases observed in our laboratory may reflect the growing at-risk population of contact lens wearers. Acanthamoeba as a genus of facultative human parasites is currently classified into 17 genotypes. Isolates belonging to seven genotypes were found to be associated with AK. One genotype in particular, T4, was found to be overrepresented in human disease. The main finding of our study is that in Poland, AK is almost always associated with the T4 genotype.